COVID-19 and the Heart: A Systematic Review of Cardiac Autopsies - Roshdy, Ashraf; Zaher, Shroque; Fayed, Hossam; Coghlan, John Gerry (Frontiers in Cardiovascular Medicine, 2021)
Abstract Importance SARS-COV-2 associated cardiac injury has been postulated secondary to several mechanisms. While tissue diagnosis is limited during the acute illness, post-mortem studies can help boost our understanding and guide management. Objective To report the cardiac tissue autopsy findings in COVID-19 decedents. Evidence Review Articles published in PubMed and Embase reporting post-mortem cardiac pathology of COVID-19 decedents till September 2020. We included adult studies excluding pre-prints. The Joanna Briggs Institute Critical Appraisal Checklist for Case Reports was used to assess quality. We extracted gross and histology data as well as the incidence of myocarditis, cardiac ischemia, thrombosis and dilatation. We also looked at the reported cause of death. (PROSPERO registration CRD42020190898) Findings 41 relevant studies identified including 316 cases. The deceased were mostly males (62%) and elderly (Median age 75, range: 22 to 97 years). The most common co-morbidities were hypertension (48%) and coronary artery disease (33%). Cardiac pathologies contributed to the death of 15 cases. Besides chronic cardiac pathologies, post-mortem examination demonstrated cardiac dilatation (20%), acute ischemia (8%), intracardiac thrombi (2.5%), pericardial effusion (2.5%) and myocarditis (1.5%). SARS-CoV-2 was detected within the myocardium of 47% of studied hearts. Conclusions and Relevance SARS-CoV-2 can invade the heart but a minority of cases were found to have myocarditis. Cardiac dilatation, ischemia, mural and micro thrombi were the most frequent findings. The systematic review was limited by the small number of cases and the quality of the studies and there is a need to standardise the cardiac post-mortem protocols.